Sunken flap following chest tube placement in the presence of ventriculopleural shunt: a case report - Stephanie Q. Liang; Fawaz Philip Tarzi; Gene Y. Sung; Roy A. Poblete (Journal of Medical Case Reports)
Abstract Background The sunken flap or sinking skin flap syndrome is a complication that can be observed following decompressive craniectomy. More rare, sinking skin flap syndrome can occur as an iatrogenic complication of pleural effusion evacuation via chest tube placement in the presence of ventriculopleural shunt. Case presentation We report the case of a Hispanic male patient in his 20s who presented to the emergency department after sustaining a penetrating gunshot wound to the head. In addition to undergoing an emergent decompressive craniectomy, a ventriculopleural shunt was subsequently placed as a treatment for hydrocephalus. Two days after shunt placement, the patient developed significant hydropneumothorax that did not respond to observational management. Owing to the severity of his hydropneumothorax, a chest tube was placed for evacuation, but he developed a sinking skin flap at the craniectomy site. The suction function of the chest tube was discontinued, and the ventriculopleural shunt pressure was increased. Within 24 hours, the skin flap reexpanded. We hypothesize that the inherently negative pressure of the pleural space combined with significant suction effect from chest tube evacuation placed him at risk of sinking skin flap syndrome despite having an antisiphon device. Conclusion Our case highlights the importance of understanding cerebrospinal fluid hydrodynamics with shunt presence and suggests a potential treatment framework for iatrogenic sinking skin flap syndrome in the presence of ventriculopleural shunt.